The Search for Induced Superconductivity Across Planar Al/EuS/InAs 2DEG Josephson Junctions - Jamo Abdi,Sherwan (2025)
This thesis investigates superconductivity in novel planar Josephson junctions fabricated from a hybrid Al/EuS/2DEG (InGaAs/InAs/InGaAs) heterostructure. Using electron-beam lithography, selective etching, and atomic layer deposition, Josephson junction devices, constrictions, and SQUID geometries were fabricated and a selection of the devices were characterized at millikelvin temperatures. The measurements revealed superconducting windows exhibiting hysteretic behavior under magnetic fields, along with asymmetric and distorted Fraunhofer interference patterns. However, unexpectedly low normal-state resistances (on the order of tens of Ohms) and notably high critical currents (10–20 µA) raised significant uncertainties regarding the origin of the observed superconductivity, questioning whether it truly results from proximity-induced superconductivity or simply unintended shorted superconducting leads. Limited gate-tunability further complicated this interpretation. Observed asymmetries and anomalies may stem from flux trapping, ferromagnetic interface effects (EuS), and structural issues due to the lack of mesa isolation. These initial findings highlight critical challenges and suggest specific avenues for refining fabrication techniques and improving device architectures. Addressing these issues will be essential for conclusively understanding superconductivity in hybrid heterostructures and advancing their potential in future quantum electronic applications
Keywords: Superconductivity Ferromagnet 2DEG EuS InAs Proximity effect Josephson Junction Induced Superconductivity Hysteresis Gates Fabrication Fraunhofer